THE ROLE OF CHANGE AGENTS IN COMMUNITY EMPOWERMENT USING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT): CASE STUDY AT DESA KALIABU, CENTRAL JAVA - Mira Azzasyofia; Isbandi Rukminto Adi; Admiral Nelson Aritonang (Indonesian Journal of Social Work, 2020)
In achieved the development in rural area, there needs to be empowerment of the rural community. The success of rural community empowerment is determined by the existence of a capable change agents to help communities improve their own strength. Desa Kaliabu, Central Java became one of the villages that succeeded in community empowerment by the utilization of Information and Communication Technology (ICT) due to the existence of change agents. Methodically using qualitative research method, this study describes the role of change agents at Desa Kaliabu in community empowerment by the utilization of ICT. This study reveals that change agents in Desa Kaliabu have educational, technical, representational, and facilitative roles and skills. Educational roles are owned consisting of Consciousness-raising, informing, and training. The technical roles consist of the ability to use computers and financial control. Meanwhile the representational roles consist of advocacy, networking, and sharing knowledge and experience. While facilitative roles seen from the existence of personal communication, utilization of skill and resources, social animation, and mediation.